2008
DOI: 10.1111/j.1582-4934.2008.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of raloxifene on breast cancer cell migration and invasion through the actin cytoskeleton

Abstract: IntroductionHormone replacement therapy (HRT) Abstract Raloxifene (RAL) is a selective oestrogen receptor modulator (SERM) approved for the prevention and treatment of osteoporosis and for the prevention of breast cancer in postmenopausal women. However, little is known on the effects of this SERM on breast cancer cell metastasis, which is the main cause of morbidity and death. Cell movement is critical for local progression and distant metastasis of cancer cells. These processes rely on the dynamic contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 28 publications
4
13
1
Order By: Relevance
“…A recent study shows that estradiol is able to promote breast cancer cell invasion and metastatization through RhoA/ROCK signaling [45]. Our results are in agreement with this finding, showing an estrogen-dependent RhoA/ROCKinduced regulation of epididymal cell motility.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study shows that estradiol is able to promote breast cancer cell invasion and metastatization through RhoA/ROCK signaling [45]. Our results are in agreement with this finding, showing an estrogen-dependent RhoA/ROCKinduced regulation of epididymal cell motility.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have confirmed that actin cytoskeleton remodeling is the basis for tumor cell migration, adhesion, and invasion272829, and a variety of molecules are involved in the regulation of actin polymerization and depolymerization, of which the LIMK gene is an important molecule3031. LIMK1 is overexpressed in a variety of malignancies including prostate, gastric, and lung cancers, and significantly promotes tumor cell invasion and metastasis323334.…”
Section: Discussionmentioning
confidence: 99%
“…The study performed by Elizabeth et al. evaluated the effects of various combinations of raloxifene, 5‐fluorouracil, and methotrexate to determine the most effective antitumor drugs combination in bone marrow and breast cancer cells . Their results indicated that late raloxifene administration (following treatment with 5‐FU/methotrexate) provides a cytotoxic advantage against breast cancer cells as bone marrow cells are protected by 5‐FU/methotrexate.…”
Section: Discussionmentioning
confidence: 99%